Leed rating system barriers in the construction sector in Northern Iraq - Shawkat, Lawand Wirya; Al-Din, Salar Salah Muhy; Kuzovic, Dusko R. (Industrija, 2017)
Northern Iraq (federal part of Iraqi Federal Republic) has witnessed a huge development in construction sector last ten years. However, there are lack of awareness and legislation regarding the sustainable construction in the building sector. The impact of construction technologies became a challenge front the serious problems of environmental crisis. The aim of the paper is to find the required mechanism to introduce sustainable practice and implement sustainable construction in the building construction sector. The main objectives in the paper are: identify the barriers in sustainable construction; investigate the law and regulations in dealing with these barriers; evaluate the application of LEED rating system in the construction sector. The research method in the paper is based on literature review and professional opinion through questionnaire. The paper list the most important barriers for implementing sustainable construction, the suggestions to apply LEED rating system, and recommendations to improve and develop sustainability in construction sector at Northern Iraq.
Keywords: Iraq; Construction; Building construction; Building